2001
DOI: 10.1038/sj.jea.7500168
|View full text |Cite
|
Sign up to set email alerts
|

Source apportionment of exposure to toxic volatile organic compounds using positive matrix factorization

Abstract: Data from the Total Exposure Assessment Methodology studies, conducted from 1980 to 1987 in New Jersey ( NJ ) and California ( CA ) , and the 1990 California Indoor Exposure study were analyzed using positive matrix factorization, a receptor -oriented source apportionment model. Personal exposure and outdoor concentrations of 14 and 17 toxic volatile organic compounds ( VOCs ) were studied from the NJ and CA data, respectively. Analyzing both the personal exposure and outdoor concentrations made it possible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 27 publications
4
23
0
Order By: Relevance
“…The factor explained 50% of the variance in the data. Results were consistent with a source apportionment analysis of the NJ and CA TEAM studies (Anderson et al, 2001), which with different statistical techniques found that aromatics are the major source of personal exposure to VOCs (resembling automobile exhaust, gasoline vapor or ETS). After tobacco smoke (partially restricted in this study), a population-based study in West Germany (Hoffmann et al, 2000) found that automobile-related activities such as driving a car or refueling were also associated with significantly increased levels of benzene.…”
Section: Factor Analysissupporting
confidence: 70%
See 1 more Smart Citation
“…The factor explained 50% of the variance in the data. Results were consistent with a source apportionment analysis of the NJ and CA TEAM studies (Anderson et al, 2001), which with different statistical techniques found that aromatics are the major source of personal exposure to VOCs (resembling automobile exhaust, gasoline vapor or ETS). After tobacco smoke (partially restricted in this study), a population-based study in West Germany (Hoffmann et al, 2000) found that automobile-related activities such as driving a car or refueling were also associated with significantly increased levels of benzene.…”
Section: Factor Analysissupporting
confidence: 70%
“…The sixth factor had high loads on 1,4-dichlorobenzene associated with deodorizers. Similarly, the TEAM studies source apportionment analysis (Anderson et al, 2001(Anderson et al, , 2002) also found that 1,4-dichlorobenzene came up as a separate factor representing mothballs and deodorizers.…”
Section: Factor Analysismentioning
confidence: 99%
“…While a number of studies have measured exposure to VOCs and aldehydes (13,14,(23)(24)(25)(26)(27)(28)(29), none have concentrated specifically on an occupational setting with intense and prolonged exposure to diesel exhaust and exhaust from other combustion sources. However, a few studies have focused on VOC and aldehyde exposures in similar microenvironments to those observed in our study, including background, traffic, and transportation depots.…”
Section: Discussionmentioning
confidence: 99%
“…If the concentration is less than or equal to the MDL provided, the uncertainty is calculated using the following equation, Unc = 5/6 × MDL; If the concentration is greater than the MDL provided, the calculation is Unc = [(Error fraction × mixing ratios) 2 + (MDL) 2 ] 1/2 . The number of factors in the PMF model was chosen based on the result from PCA/APCS model [55].…”
Section: Source Apportionment With Positive Matrix Factorization (Pmf)mentioning
confidence: 99%